2021
DOI: 10.2196/27276
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Extensively Drug Resistant Typhoid Fever Among Children in Karachi: Case-Control Study

Abstract: Background Extensively drug resistant typhoid fever (XDR-TF) has been responsible for an ongoing outbreak in Pakistan, which began in November 2016. Objective This study aimed to determine the risk factors associated with XDR-TF. Methods This age- and sex-matched case-control study was conducted during May-October 2018 in Karachi. All patients with XDR-TF were identified from the laboratory-based surveillanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…This observation is in agreement with that of a retrospective surveillance study of enteric fever cases conducted across all regions of Pakistan [22]. A recently published study from Karachi also showed that adults are less susceptible to typhoid than are children aged 5-15 years [31]. We did not detect any case of typhoid or paratyphoid in children under 2 years of age in this location.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is in agreement with that of a retrospective surveillance study of enteric fever cases conducted across all regions of Pakistan [22]. A recently published study from Karachi also showed that adults are less susceptible to typhoid than are children aged 5-15 years [31]. We did not detect any case of typhoid or paratyphoid in children under 2 years of age in this location.…”
Section: Discussionsupporting
confidence: 93%
“…Herein, more boys than girls were infected with S. Typhi but the sample size was insufficient to enable a statistically relevant analysis. However, the trend for greater susceptibility of male children to typhoid is consistent with other studies in which gender was considered as a risk factor for contracting enteric fever [31][32][33]. This may be associated with gender differences relating to level of exposure, wherein boys spend more time playing and eating outdoors.…”
Section: Discussionsupporting
confidence: 89%
“…Vigho et al found community water supply and street food are the main risk factors for XDR typhoid. 19 Focus on the supply of safe potable drinking water and strict policy of street food safety should be implemented by the authorities. Vaccination against salmonella is also imperative.…”
Section: Discussionmentioning
confidence: 99%
“…Vigiho et al in 2021 determined the risk factors associated with extensively drug-resistant typhoid fever in Pakistani children. 16 They revealed that patients using community water supply and eating from street vendors had more chances of having the drugresistant disease. Our study design and parameters differed from that of Vigiho et al but the use of boiled water was not significantly associated with the presence or absence of multi-drug resistant typhoid in our study participants.…”
Section: Bhutta Et Al Conducted a Study On Paediatric Patients Presen...mentioning
confidence: 99%